Workplace temporalities - Rubin, Beth A., 1955- (Amsterdam ; Boston : Elsevier JAI, 2007)
The global, 24/7 economy and the organizational changes it has generated have enormous implications for the organization, experience and use of time in (and out of) the workplace. In addition to eroding the boundary between home and work, creating time pressures both within and outside of the workplace, the need for businesses to compete in a 24/7 global economy has re-problematized time in the workplace. Drawing on sociology, labor economics, organizational behavior and social history, the papers in this volume examine either empirically or theoretically, a variety of aspects of time in the workplace. Contributors to this volume examine issues surrounding the distribution of and struggle over work hours and how these vary across a number of factors including race, class, occupation and other structural components of work. They examine temporal structures within organizations including inequities in flexible scheduling, entrainment and work teams, polychronicity, and how changing temporal structures affect professionalism and expertise. They also consider the way in which changing uses and organization of work time, in the context of economic instability and globalization, affect the difficulties of reconciling work and family. At the more micro-level, the papers consider individuals' perceptions and constructions and intersubjective constructions of time. To varying degrees, the authors speak to the policy implications or strategies for managing new times. Taken as a whole, these papers shed light on the way in which globalization and the emergence of a 24/7 economy have altered the ways, times, and meanings of time at work. This book series is available electronically online.
Includes bibliographical references.
Description based on print version record.
Keywords: Work -- Social aspects; Hours of labor; Sociology: work & labour; Social Science -- Sociology -- General